A prospective observational study of associated anomalies in hirschsprung’s disease - Patole, Monali Madhukar; Patole, Mandar Madhukar; Paul, Subhasish (International Journal of Contemporary Pediatrics, 2019)
Background: Hirschsprung’s Disease (HSCR) is the commonest congenital gut motility disorder and is characterized by the absence of ganglion cells in a variable length of the distal gut. According to literature , HRSCD may be associated with a chromosomal abnormality or other congenital anomalies in approximately 20% of cases HSCR appeared to be a multifactorial malformation with low, sex dependent penetrance and variable expression according to the length of the a ganglionic segment, suggesting the involvement of one or more gene (s) with low penetrance. So far, eight genes have been found to be involved in HSCR. This frequent congenital malformation now stands as a model for genetic disorders with complex patterns of inheritance. The objective of this study was to collect and study personal and family history and any information regarding known associated anomalies in patients diagnosed as Hirschsprung's disease. Methods: Here author present a series of 89 consecutive HSCR patients who were admitted or attended the Pediatric Surgery OPD of in a tertiary care Government medical college, who were evaluated for associated malformations with the help of available non-invasive investigation. Results: Congenital heart diseases and Down’s syndrome were the two most common associated anomalies. Genitourinary anomalies, Limb anomalies and central nervous system anomalies were other associated anomalies. Conclusions: This study confirmed the underestimation of certain associated anomalies in Hirschsprung patients, such as CNS anomalies. Based on the results of this study, in addition to meticulous general examination author suggest performing cardiologic assessment in patients diagnosed with Hirschsprung’s disease based on clinical features and according to the standards of care adopted for the general population.